1981
DOI: 10.1007/bf00008283
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selected physical and chemical factors on attached diatoms in the Uintah Basin of Utah, U.S.A.

Abstract: The relat onsh ps of d atom spec es to selected phys cal and chem cal parameters n the streams of the U ntah Bas n of Utah were stud ed through four seasons of [1977][1978] . N che center grad ent analys s, cluster analys s and correlat on analys s were performed . Achnanthes m nut ss ma, Cyclotella menegh n ana, Cymbella m nuta var . latens, Frag lar a capuc na, and Nav cula secreta var . ap culata appear to be nd cator spec es of h gh or low levels of certa n water qual ty parameters . Several other spec es … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1981
1981
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
4
1
Order By: Relevance
“…In this study no relationship was found between concentrations of nutrients in the water and biofilm state and, while several studies have highlighted the importance of nutrients in determining algal biomass (Everson et al . 1981;Peterson et al .…”
Section: Discussioncontrasting
confidence: 72%
“…In this study no relationship was found between concentrations of nutrients in the water and biofilm state and, while several studies have highlighted the importance of nutrients in determining algal biomass (Everson et al . 1981;Peterson et al .…”
Section: Discussioncontrasting
confidence: 72%
“…(Evenson et al, 1981) . We have additionally shown that such responses may relate to seasonal differences .…”
Section: Indicator Speciesmentioning
confidence: 99%
“…Baumann & Wingett (1975) studied the water quality and fauna of the White River, Uintah County, Utah . Algal studies have been performed by Johansen (1974), Johansen & Rushforth (in press), and Evenson et a!. Algal studies have been performed by Johansen (1974), Johansen & Rushforth (in press), and Evenson et a!.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have related diatom community composition to environmental variation (e.g. Evenson et al ., 1981; Chessman, 1986; Sabater, Sabater & Armengol, 1988; Ten Cate, Maasdam & Roijackers, 1993; Leland, 1995; Pan et al ., 1996), but few have specifically focused on the effects of urbanization. Most studies investigating urban effects on diatom communities have been conducted in cities where sanitary sewage is a large component of runoff into the receiving streams (Nather Khan, 1990; Lobo, Katoh & Aruga, 1995).…”
Section: Introductionmentioning
confidence: 99%